Precarious Employment and Occupational Health and Safety Regulation in Quebec - Lippel, Katherine (Precarious Employment: Understanding Labour Market Insecurity in Canada, 2006)
[Analyzes] existing legislation, law and legal literature on the application of occupational health and safety and on workers' compensation legislation in Quebec. [Argues] there are very few tools available to examine regulatory effectiveness from a legal perspective...[and that] it is crucial for legal researchers to join with researchers determining health effects. --From editor's introductory chapter, p. 38.
Keywords: Labor Unions; Labor laws and legislation; Labor market; Temporary employment